INTERVENSI HIGH INTENSITY INTERVAL TRAINING (HIIT) TERHADAP PENURUNAN KADAR KOLESTEROL MAHASISWA PROGRAM STUDI ILMU KEOLAHRAGAAN UNIVERSITAS NEGERI PADANG: THE EFFECT OF HIGH INTENSITY INTERVAL TRAINING (HIIT) INTERVENTION ON CHOLESTEROL LEVELS IN SPORT SCIENCE STUDENTS PADANG STATE UNIVERSITY - reyhan aditya pratama,; Permata Sari, Anggun; Syafrianto, Donal; Selviani, Iit (Jurnal IKEOR, 2026)
The purpose of this research is to look at how total cholesterol levels in students in the Sport Science Study Program at Universitas Negeri Padang are affected by just one acute HIIT session. An acute pre-post test technique was utilized in the quantitative, quasi-experimental research methodology. Purposive sampling was used to choose the 25 participants for the study, who all met the requirements of a sedentary lifestyle and somewhat elevated cholesterol levels. Using a modified jogging interval protocol that included three sets, each with a work phase at 65–75% of HRmax and an active recovery phase at 65–40% of HRmax, High Intensity Interval Training intervention was carried out on a treadmill. The Autocheck instrument was used to assess cholesterol levels prior to and 40 minutes following the treatment. The Paired Sample T-Test was the statistical technique employed. According to the results, total cholesterol levels decreased significantly with High Intensity Interval Training (t = 4.722, p = 0.000 < 0.05), with an average reduction of 18.12 mg/dL (8.09%) between the pre-test value of 223.96 mg/dL and the post-test value of 205.84 mg/dL. These results demonstrate that in young adults leading sedentary lives, a single High Intensity Interval Training session can successfully lower cholesterol levels in the short term.